TSUNAMI-MAGNETIC SIGNALS AND MAGNETIC ANOMALY GENERATED BY TSUNAMI WAVE PROPAGATION AT OPEN SEAS (Department of Physics, Faculty of Mathematics and Natural Sciences, 2017)
This research examines the generation of tsunami-induced magnetic signals, where local magnetic anomaly were measured as variations in the vertical bz and horizontal bH components of the secondary field. The maximum amplitudes of bz and bH were analytically estimated and compared to magnetogram provided by INTERMAGNET and BCMT for the 2010 Chilean, the 2011 Tohoku, the 2010 Mentawai and the 2004 Aceh tsunamis. For the first two cases, frozen-flux theory was used to estimate bz and bH where the phase lag between bz and bH was ?/2, relevant to time interval of T/4 between the two signals. For the Mentawai case, oceanic diffusion was unignored and bz significantly deviated from that calculated using the theory. However, the data from Mentawai where bz ? 2 nT were in good agreement with bz generated by large tsunamis occurring in regions near the equator and with magnetogram from the Aceh event.